Efektifitas pelatihan perawatan diri terhadap dukungan emosional dan instrumental keluarga penderita kusta - Wulandari, Listyorini; Suswardany, Dwi Linna; Firnawati, Artika Fristi (Jurusan Keperawatan FIKES UNSOED, 2011)
Background. The leprosy patients in a deform condition are still many, so that self care is needed in order to prevent this aggravating condition. Objective. The aim of this research was to evaluate the effectiveness of self care training towards family support improvement to leprosy patients in Harapan Kita Association, Padas Subdistrict, Ngawi Regency. Method. This research used pre experiment method with static group comparation approach. There were treatment group and control group in this research. The treatment group were leprosy patients that attended self care training as many as 43 respondents while the group of control were leprosy patients that did not attend self care training as many as 35 respondents. The sampling method for treatment group was exhaustive sampling while for group of control used purposive sampling. The data were analysed using t-test independent. Result. The result indicated that self care training was effective for improving emotional support (p= 0.025) and instrumental support (p= 0.044) of the family. However, it was not effective for improving informative support (p = 0.792) and appreciation support (p = 0.354) of the family. Conclussion. Self care training is effective for improving emotional and instrumentaal support but not for informative and appreciation.